An Irish country girl - Taylor, Patrick, 1941- (New York : Forge, 2010)
Presents the story of the early life of Kinky Kincaid, once known as Maureen O'Hanlon, a farmer's daughter growing up in the hills and glens of 1920s County Cork, Ireland, who had a gift for seeing faries, spirits, and the dreaded banshee.
"A Tom Doherty Associates book."
Keywords: Young women -- Ireland -- Fiction; Pastoral fiction